Application of Ergonomic Principles in Production Area Layout Design to Improve Work Efficiency at CV. Adi Makmur Metalindo - Fragastia, Vidi Agung; Bukhori, Alan Akbar; Albani, Khairul (Publikasi Pengabdian Masyarakat, 2025)
CV. Adi Makmur Metalindo is a metal manufacturing company with physically intensive work activities in its production area. Based on initial observations, the layout of the production area has not fully applied ergonomic principles, resulting in inefficient workflow and health complaints among workers. This program aims to analyze the existing layout conditions, redesign the production area based on ergonomic principles, and measure the impact of these changes on work efficiency and comfort. The implementation method includes field observations, measurement of distances and time between work activities, posture analysis using the REBA method, and layout redesign using the Systematic Layout Planning (SLP) approach. As part of the impact evaluation, pre-test and post-test questionnaires were distributed to 10 workers to assess their perceptions before and after the proposed improvements. The analysis results show that the new layout design successfully reduced travel distance and process time, as well as improved the placement of work tools that were previously inefficient. The questionnaire results revealed a significant increase in workers’ perceptions of workflow efficiency, posture comfort, and satisfaction with the layout—showing an average score increase of 1.4 to 1.7 points. In addition, the program also raised awareness among workers about the importance of ergonomics in the workplace. In conclusion, the application of ergonomic principles in the reorganization of the production layout had a positive impact on both work efficiency and comfort. This program can serve as an applicable model of ergonomic implementation that benefits other small and medium-sized industries in creating a more productive and sustainable work environment.